2012
DOI: 10.4314/bajopas.v5i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Development of Host Plant Resistance to Infestation by Aphid (<em>Aphis Craccivora</em> Koch) in Cowpea (<em>Vigna Unguiculata</em> [L] Walp)

Abstract: A study was carried out at International Institute of Tropical Agriculture (IITA) Kano station during 2009 and 2010 growing season, to screen fifty two (52) cowpea varieties for resistance to aphids (Aphis craccivora) attack. It was found that only seven (7) varieties were highly resistant, nine (9) were highly susceptible and the remaining thirty six (36) varieties were neither resistant nor susceptible (intermediate) to aphids attack. Five (5) varieties were selected from the two extremes for multiple crosse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Thus, when cross-breeding used genotypes CE-315 and TE97-304G-12 as parents, susceptible offsprings were generated, as with 'BR 17-Gurguéia', which had CE-315 as a parent. According to Babura & Mustapha (2012), when crossing V. unguiculata using resistant and susceptible genotypes to A. craccivora in the F 1 , offsprings that are highly resistant to aphids will be obtained in the F 2 and subsequent backcrosses. This is because, in A. craccivora, resistance to cowpea aphid is linked to a dominant gene.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, when cross-breeding used genotypes CE-315 and TE97-304G-12 as parents, susceptible offsprings were generated, as with 'BR 17-Gurguéia', which had CE-315 as a parent. According to Babura & Mustapha (2012), when crossing V. unguiculata using resistant and susceptible genotypes to A. craccivora in the F 1 , offsprings that are highly resistant to aphids will be obtained in the F 2 and subsequent backcrosses. This is because, in A. craccivora, resistance to cowpea aphid is linked to a dominant gene.…”
Section: Resultsmentioning
confidence: 99%
“…'BRS Guariba', in which the cultivar would transfer the resistance gene to its progeny. According to Babura & Mustapha (2012), when crossbreeding of cowpea varieties susceptible to the cowpea aphid is carried out with resistant materials, it is possible to produce highly resistant progenies, implying that the transmission of the gene conferring cowpea resistance to A. craccivora is heritable. Silva et al (2012) evaluated the genetic diversity between cowpea genotypes with resistance to the cowpea aphid, and the best combinations among resistant genotypes, and confirmed that 'BRS Guariba' is favorable to genetic combinations and suitable for breeding programs as a source of resistance to the aphid.…”
Section: Resultsmentioning
confidence: 99%